من مكونات الخطاب الروائي في رواية (رسمت خطاً في الرمال) للروائي: هاني الراهب الراوي، والمروي، والمروي له. - مغربي, فاروق إبراهيم; دنده, ديالا حليم (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تتصدى رواية (رسمت خطاً في الرمال) لرصد الحراك السياسي/ الاجتماعي لدول الخليج العربي في مرحلة مفصلية من تاريخها تتحدّد بفترة غزو العراق للكويت، ودخول الجيوش الأمريكية إلى دولة الكويت بذريعة حمايتها من عدوان شقيقتها العربية عليها، وكل ذلك من أجل الوصول إلى النفط العربي ــــــ المكتشف حديثاً آنذاك ــــــــ والسيطرة عليه بأي ثمن. وعلى الرغم من هذه المرجعية الواقعية، فإن خطاب الرواية الفانتازي وعوالمها السحرية، هما اللذان كانا سلاح الكاتب في نقده الواقع العربي النمطي المأزوم، الذي اتفق عليه بحكم العادة. نقداً لاذعاً، والعمل على استبداله بعالم فني متخيل من خلال بنية سردية استطاعت، مابين الإقناع والإمتاع، أن تمنح الكلمة بعدها السياسي، وتترك لقارئها حرية تلقي مايريد من أفكار غير مشروطة، والتمتع بفن غير محدود، بعد استثمار مكونات الخطاب الروائي، وتسخير التقنيات الفنية والجمالية والتجارب الواقعية ضمن قالب فني قادر على تحقيق الغاية المنشودة منه. Hani al-Raheb’s novel (Rasamt Khatan Fy Alremal) (I drew a line in the sand) addresses the political and social movement of Gulf States in a critical stage of its history. Namely, it is the period of Iraq's invasion of Kuwait and the entry of US armies to the State of Kuwait under the pretext of protecting it from the aggression of its Arabic sister. All this in order to reach the Arab oil - newfound then – and to control it at any price In spite of this realistic reference, the fantastic narrative and the magical worlds of the novel are the writer’s weapon in his sharp satire on a traditional typical tense Arabic World. The writer replaces this reality with a narrative structure that uses conviction and entertainment to give the word its political damnation giving the reader -in the same time- the freedom to accept whatever he wants from its unconditional thoughts and to enjoy the unlimited art. To do this, the novelist takes advantages of the narrative components using the aesthetic and artistic techniques and the realistic experiments in an artistic pattern to reach his aim.